PENERAPAN STRATEGI PEMBELAJARAN EKSPOSITORI DALAM PENGELOLAAN KELAS PADA MATA PELAJARAN BAHASA INDONESIA KELAS II SD NEGERI 008 /VI LUBUK GAUNG I TAHUN PELAJARAN 2025/2026 - Zamdani; Endang Komara; Teti Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of effective classroom management in supporting the success of Indonesian language learning in lower elementary grades. Based on preliminary observations, the classroom conditions were not fully conducive, as indicated by decreased student focus and participation during the learning process. Therefore, an appropriate learning strategy is needed, one of which is the expository learning strategy that emphasizes systematic, structured, and teacher-centered delivery of material.This study aims to describe the implementation of the expository learning strategy in classroom management in the Indonesian language subject for grade II students at SD Negeri 008/VI Lubuk Gaung I in the 2025/2026 academic year. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation.The results show that the implementation of the expository learning strategy was carried out through several stages, including introduction, material presentation, question-and-answer interaction, and practice and evaluation. This strategy helped teachers manage the classroom effectively, create a more orderly and conducive learning environment, and improve students’ understanding of the learning material. Therefore, the expository learning strategy is proven to be effective in supporting classroom management and enhancing the quality of Indonesian language learning in first-grade elementary school.